Flank Versus Prone and Supine Positions in Percutaneous Nephrolithotomy: A Systematic Review of Stone Clearance and Perioperative Outcomes - Yusuf, Yusuf; Zutianda, Wahyu; Syafridon, M Fadhil (PT FORMOSA CENDEKIA GLOBAL, 2025)
Percutaneous nephrolithotomy (PCNL) is traditionally performed in the prone position, though this may pose anesthetic risks for high-risk patients. The flank position has been proposed as an alternative, but evidence remains limited. This systematic review of seven studies (2008–2023) found that flank PCNL achieves stone-free rates of 85–91%, comparable to prone positioning, with similar complication profiles and indications of reduced bleeding and respiratory issues. Operative time varied across studies, while hospital stay remained consistent. Overall, the findings support flank PCNL as a safe and effective alternative, though small sample sizes and methodological heterogeneity highlight the need for larger multicenter research.